1994
DOI: 10.1172/jci117098
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of leukocyte rolling with polysaccharide fucoidin prevents pleocytosis in experimental meningitis in the rabbit.

Abstract: Inflammatory recruitment of leukocytes into the cerebrospinal fluid (CSF) during bacterial meningitis has been shown to contribute significantly to the neurological damage commonly associated with this serious disease. In this study we tested whether or not inhibition of leukocyte rolling, a precondition for firm leukocyte adhesion to vascular endothelium in vivo, may reduce CSF leukocyte recruitment and associated inflammatory changes in rabbits with experimental meningitis. As documented by intravital micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 54 publications
3
86
2
Order By: Relevance
“…The strong reduction in the number of adherent cells in the presence of a modest (20-30%) inhibition of rolling interactions in the synovial venules of fucoidin-treated mice was somewhat in conflict with previous in vivo findings that fucoidin strongly inhibited cell rolling, but not firm adhesion (23)(24)(25). The discrepancy prompted us to examine whether the selectin antagonist reduced firm adhesion by disrupting existing adhesion interactions (thus resulting in an enhanced detachment rate) or by preventing the arrest and subsequent firm adhesion of rolling cells.…”
Section: Effect Of Fucoidin An Inhibitor Of Selectinmediated Cell Rocontrasting
confidence: 70%
“…The strong reduction in the number of adherent cells in the presence of a modest (20-30%) inhibition of rolling interactions in the synovial venules of fucoidin-treated mice was somewhat in conflict with previous in vivo findings that fucoidin strongly inhibited cell rolling, but not firm adhesion (23)(24)(25). The discrepancy prompted us to examine whether the selectin antagonist reduced firm adhesion by disrupting existing adhesion interactions (thus resulting in an enhanced detachment rate) or by preventing the arrest and subsequent firm adhesion of rolling cells.…”
Section: Effect Of Fucoidin An Inhibitor Of Selectinmediated Cell Rocontrasting
confidence: 70%
“…The effects of fucoidan on survival rate and spleen function were prophylactic, rather than therapeutic, suggesting that fucoidan requires time to protect target cells against the harmful effects of LPS. Based on previous studies, fucoidan blocks selectin-dependent leukocyte adhesion/rolling [13,14] and inhibit microvascular thrombus formation [15]. It is thus suggested that fucoidan may affect blood circulation dysfunction by LPS in mice.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, inhibition of selectin binding to sialyl Lewis X by the polysaccharide fucoidin, results in reduction of PMN rolling and extravasation. 40,41 These sugars may be expressed on several membrane proteins, 42 including those mediating L-selectin and P-selectin binding to their counterligands. 37 It is of interest that a recent study has reported a role for complex sugars in mediating the anti-inflammatory effects of heparin derivatives.…”
Section: Discussionmentioning
confidence: 99%